Post-COVID in Patients with Obesity: A Narrative Review - Vásquez-Granda, Janeth; Tarrillo-Olivos, Jessy C.; Pereyra-Urbina, Naomy R.; P- Santa-Cruz, Jhanina Paola; Cabanillas-Carrero, Yajahira M.; Álvarez-Manrique, Víctor; Sairitupa-Sanchez , Liset Z.; Morales-García, Wilter C. (Salud Integral y Comunitaria, 2025)
Objective: This study aims to conduct a brief literature review on post-COVID-19 complications in obese patients.Design: A literature review based on a narrative synthesis.Data Sources: The databases consulted include Science Direct, Scopus, Scielo, Google Scholar, and PubMed.Study Selection: Multiple articles were selected, applying inclusion criteria focused on post-COVID-19 complications in obese patients, with publications ranging from 2020 to 2024. Irrelevant studies were excluded. The final selection included articles from 10 different countries.Data Extraction: From each study, key data were extracted, including research design, population characteristics, and main reported complications. The information was organized narratively to facilitate comparison of findings across studies.Results: Out of 261,357 articles, 15 relevant articles were selected for the review. These articles were published in 10 countries, as follows: Spain (3 middle-income and 1 lower-middle income), Italy (1 lower-middle income, 1 high-income, and 1 mixed-income), India (2 middle and lower income), Russia (1 middle income), Japan (1 high, middle, and low income), Germany (1 middle income), United States (1 middle income), Mexico (1 middle income), Brazil (1 middle income), and China (1 high and middle income). The findings indicate that socioeconomic inequalities tend to increase the risk of COVID-19-related mortality.Conclusion: COVID-19 is associated with type 2 diabetes, an increased risk of coronary problems, hypertension, and nerve damage such as polyneuropathy, affecting muscle strength and increasing the mortality rate in respiratory diseases such as COPD, leading to lung damage and fibrosis. Treatment should be comprehensive, including vaccines, respiratory exercises, and physiotherapy, where the drug Veklury (remdesivir) has shown efficacy in accelerating recovery and strengthening the immune system. Additionally, post-COVID conditions such as anxiety, depression, and persistent respiratory issues should be addressed.